2020
DOI: 10.1002/pmic.202000198
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in the COVID‐19 Battlefield: First Semester Check‐Up

Abstract: Proteomics offers a wide collection of methodologies to study biological systems at the finest granularity. Faced with COVID‐19, the most worrying pandemic in a century, proteomics researchers have made significant progress in understanding how the causative virus hijacks the host's cellular machinery and multiplies exponentially, how the disease can be diagnosed, and how it develops, as well as its severity predicted. Numerous cellular targets of potential interest for the development of new antiviral drugs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…The nucleocapsid (N protein-RNA complex) protects and organizes the RNA molecule into the viral lumen. Interestingly, structural studies of viral particles revealed an extensive heterogeneity of its molecular architecture [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleocapsid (N protein-RNA complex) protects and organizes the RNA molecule into the viral lumen. Interestingly, structural studies of viral particles revealed an extensive heterogeneity of its molecular architecture [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have also recently shown how shotgun proteomics of SARS-CoV-2 infected cells can be of help to optimize whole viral particle antigen production for vaccines [ 11 ]. Proteomics has been shown quite useful to understand the molecular mechanisms deployed by the virus to hijack the host machinery and to define relevant markers for diagnostics [ 1 ]. Interestingly, RNAseq was used to determine the transcriptome of SARS-CoV-2 grown in Vero E6 cells, a cell line widely used to propagate the virus, and evidenced an in-frame deletion of the gene encoding the Spike glycoprotein [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the COVID-19 pandemic has led to the launch of a large number of clinical studies 42 , to our knowledge, this is the rst time the composition and functionality of gut microbiota have been analysed by differential metaproteomics, with samples distinguished based on the presence of SARS-CoV-2 RNA in the intestinal tract. Interestingly, even in stool specimens containing high levels of viral genetic material, no SARS-CoV-2-derived peptides were detected in our discovery metaproteomics approach.…”
Section: Discussionmentioning
confidence: 99%
“…This negative result could be ascribed to the complexity of the samples and a lack of sensitivity of our approach. Indeed, although targeted proteomics can successfully detect SARS-CoV-2 proteins in nasopharyngeal swabs and gargle samples [43][44][45] , viral proteins have never been detected by discovery proteomics approaches applied to complex matrices 42 . Alternatively, these samples may only contain RNA fragments as previously reported for faeces collected at later time points following disease onset 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, as a result of the SARS‐CoV‐2 pandemic, MS‐based proteomics is discussed as an alternative method for virus diagnostics. In particular PRM has been suggested as the method of choice to detect SARS‐CoV‐2 proteins from patient samples like naso‐ and oropharyngeal swabs [9,1315,16,17]. To simulate a positive patient sample, we spiked cell culture‐derived SARS‐CoV‐2 in a negative oropharyngeal swab to a final cT value of about 16.…”
Section: Figurementioning
confidence: 99%